Effects of a phase IV home-based cardiac rehabilitation program on cardiorespiratory fitness and physical activity - Noites, Andreia (2017)
Cardiovascular diseases are the leading cause of death globally and sedentary lifestyle is one of the main risk factors. Home-based cardiac rehabilitation (CR) programs appear to be effective to improve exercise tolerance. The aim of the study, therefore, was to evaluate the effects of a phase IV (maintenance) home-based CR program on cardiorespiratory fitness and daily physical activity of patients recovering from an acute myocardial infarction.